Recommendations for the use of cardiac troponin measurement in acute cardiac care - Kristian Thygesen; Johannes Mair; Hugo A. Katus; Mario Plebani; Per Venge; Paul Collinson; Bertil Lindahl; Evangelos Giannitsis; Yonathan Hasin; Marcello Galvani; Marco Tubaro; Joseph S. Alpert; et al. (2010)
The release of cardiomyocyte components, i.e. biomarkers, into the bloodstream in higher than usual quantities indicates an ongoing pathological process. Thus, detection of elevated concentrations of cardiac biomarkers in blood is a sign of cardiac injury which could be due to supply–demand imbalance, toxic effects, or haemodynamic stress. It is up to the clinician to determine the most probable aetiology, the proper therapeutic measures, and the subsequent risk implied by the process. For this reason, the measurement of biomarkers always must be applied in relation to the clinical context and never in isolation. There are a large number of cardiac biomarkers, but they can be subdivided into four broad categories, those related to necrosis, inflammation, haemodynamic stress, and/or thrombosis. Their usefulness is dependent on the accuracy and reproducibility of the measurements, the discriminatory limits separating pathology from physiology, and their sensitivity and specificity for specific organ damage and/or disease processes. In recent years, cardiac biomarkers have become important adjuncts to the delivery of acute cardiac care. Therefore, the Working Group on Acute Cardiac Care of the European Society of Cardiology established a committee to deal with ongoing and newly developing issues related to cardiac biomarkers. The intention of the group is to outline the principles for the application of various biomarkers by clinicians in the setting of acute cardiac care in a series of expert consensus documents. The first of these will focus on cardiac troponin, a pivotal marker of cardiac injury/necrosis.